Vocational Training in Food Service to Promote Independence for People with Sensory Disabilities in Ear and Speech - Syahabuddin, Qurratul A’yun; Kardeti, Denti; Susila, Nandang (Journal La Sociale, 2025)
This research aims to investigate the process of culinary vocational training in fostering independence for deaf and speech-impaired individuals at Sentra Mulya Jaya, East Jakarta. The study was conducted using a descriptive qualitative approach. The research was held at Sentra Mulya Jaya, with informants including three trainees, one vocational instructor, and one social worker. Data were collected through in-depth interviews, participant observation, and documentation, with analysis following the interactive model of Miles and Huberman. The findings show that the training effectively promotes independence across emotional, economic, intellectual, and social aspects. It provides technical skills and a supportive environment, enabling trainees to manage emotions, earn income, and interact socially without over-reliance on others. The conclusion is that vocational training is an effective strategy for empowering deaf and speech-impaired individuals and promoting their self-reliance